Nuevo mapa de actores en Bolivia: Crisis, polarización e incertidumbre (2019-2020). Libro de Souverein y Exeni - Ichuta Nina, Carlos Ernesto (El Colegio de México, 2024)
This work presents a critical review of the book New map of actors in Bolivia: Crisis, polarization and uncertainty  (2019-2020), coordinated by Jan Souverein and José Luis Exeni. After exposing the strong ideas of the articles that compose it, our reading identifies a tendency in them to reiterate dominant discourses in the field of common sense that we attribute to epistemological problems related to the lack of theorization and the definition of a methodological strategy, although in the specific order of events the book would constitute a document of great value.